(3GdahGFO GdhGajI NGJeIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s ((3Ydj Hf cQHdGFj SHMGfhQOjs)
(3ChdgG (B:s
(3HSe Gddg(B...(3bO LQJ YGOI GdCUhdjjf HJYQja CUhd Gdabg HGdeYfjjf GdEVGaj hGdYdej(B...s
(3BNQgG (B:s
...(3GYJeGO GdCUMGH Ydi cJGH GHf HGHhjI djS JbdjOG Hd GLJgGO dhLhO GdSHH GdeDOj Edjg (B...(3GdMeO ddg bO JeJ GdahGFO GdhGajIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B113s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B740s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs